Drug Survival and Long-term Outcome of Tofacitinib in Patients with Alopecia Areata: A Retrospective Study - Jundong Huang; Sihan Deng; Ji Li; Yan Tang; Fangfen Liu; Yu Liu; Shijia Rao; Wei Shi (Medical Journals Sweden, 2023)
Several non-randomized clinical trials and retrospective studies have demonstrated encouraging efficacy and well-tolerated safety of tofacitinib in the treatment of alopecia areata. However, there are scarce data on a large cohort of patients with alopecia areata in long-term real-world practice. This single-centre, retrospective, observational cohort study included 126 patients with alopecia areata treated with tofacitinib between February 2021 and December 2022. The aims of this study are to evaluate drug survival, effectiveness and safety of tofacitinib for treatment of alopecia areata, and to identify potential factors influencing long-term outcomes. Median duration of treatment was 23.00 (interquartile range (IQR) 15.00, 47.25) weeks. Median all-cause survival time of 126 patients treated with tofacitinib was 44 weeks (95% confidence interval (95% CI) 36.3, 51.7), and the all-cause drug retention rate at 12 weeks, 24 weeks and 48 weeks were 90.0%, 66.4% and 42.3%, respectively. The most common reason for discontinuation was complete remission/satisfaction. A total of 80 patients treated with tofacitinib for over 6 months were included in the efficacy analysis, the overall complete response rate at 24 weeks was 33.8% (27/80). No life-threatening serious adverse events occurred. Sex is an independent risk factor in predicting patient outcomes. This real-world study confirmed the high effectiveness and acceptable safety profile of tofacitinib in alopecia areata, with a satisfactory drug survival rate, and provides supporting data for the clinical application of tofacitinib in Chinese patients with alopecia areata.